2016
DOI: 10.1002/ehf2.12099
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with haematological and breast cancer (1996–2009) who died of heart failure‐related causes after cancer therapy

Abstract: AimsTo describe the characteristics and time to death of patients with breast or haematological cancer who died of heart failure (HF) after cancer therapy. Patients with an index admission for HF who died of HF‐related causes (IAHF) and those with no index admission for HF who died of HF‐related causes (NIAHF) were compared.Methods and resultsWe performed a linked data analysis of cancer registry, death registry, and hospital administration records (n = 15 987). Index HF admission must have occurred after canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The time from cancer diagnosis to cardiotoxicity in this cohort was between 0 and 18 years with mean time to death of 5 years for 16 patients. Mortality from cardiotoxicity has been demonstrated to be higher than both cancer and CVD alone [36].…”
Section: Discussionmentioning
confidence: 99%
“…The time from cancer diagnosis to cardiotoxicity in this cohort was between 0 and 18 years with mean time to death of 5 years for 16 patients. Mortality from cardiotoxicity has been demonstrated to be higher than both cancer and CVD alone [36].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HF, many different co‐morbidities can influence the patients' burden of disease . Common co‐morbidities in patients with HF include iron deficiency, anaemia, liver dysfunction, chronic kidney disease, central sleep apnoea, chronic obstructive pulmonary disease, sexual dysfunction, cachexia, sarcopenia, anorexia, and also cancer . Professor Rudolf De Boer from Groningen, the Netherlands, presented several studies, which have shown that cancer patients have an increased risk to develop HF and that patients with both, cancer and HF, demonstrate even worse prognosis than both diseases alone .…”
Section: The Intersection Between Cardiology and Oncologymentioning
confidence: 99%
“…They seem more important in HFpEF and HFmrEF, whereas HFrEF patients have more often CAD as the main cause of HF . Co‐morbidities are usually divided into cardiovascular, such as hypertension, CAD, atrial fibrillation, stroke, and non‐cardiovascular, such as cancer, chronic renal dysfunction, obstructive lung disease, sleep apnoea, iron deficiency, anaemia, sarcopenia, anorexia, frailty, cachexia, liver dysfunction,diabetes mellitus, obesity, and psychiatric disorders . They are often associated with an increased risk of HF in initially asymptomatic patients as they may cause or favour the development of cardiac dysfunction.…”
Section: Co‐morbiditiesmentioning
confidence: 99%